2003
DOI: 10.1242/jcs.00793
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD82 regulates compartmentalisation and ligand-induced dimerization of EGFR

Abstract: We have previously shown that CD82, a transmembrane protein of the tetraspanin superfamily is associated with EGFR and has a negative effect on EGF-induced signalling (Odintsova, E., Sugiura, T. and Berditchevski, F. (2000) Curr. Biol. 10, 1009-1012). Here we demonstrate that CD82 specifically attenuates ligand-induced dimerization of EGFR. The recombinant soluble large extracellular loop of CD82 has no effect on the dimerization thereby suggesting that other parts of the protein are required. Although CD82 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 56 publications
3
122
0
Order By: Relevance
“…16 Tetraspanins are also known to form a specific kind of membrane domains, 46 interact with GSL 18,47 and modulate EGFR signaling. 48 Therefore, TI-VAMPdependent regulation of EGFR may result from its role in transport of components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…16 Tetraspanins are also known to form a specific kind of membrane domains, 46 interact with GSL 18,47 and modulate EGFR signaling. 48 Therefore, TI-VAMPdependent regulation of EGFR may result from its role in transport of components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 To investigate whether c-Met-CD82 complex is a part of the large cluster of the CD82 protein complex, we performed immunoprecipitation experiments using the anti-c-Met and anti-CD82 antibodies.…”
Section: Cd82/kai-1 Associates With C-met On Carcinoma Cellsmentioning
confidence: 99%
“…Tetraspanins lack intrinsic activity and their effects are mediated by protein interactions. Several different proteins have been shown to associate with CD82 (Yunta and Lazo, 2003), including a3b1, a4b1, a5b1, and a6b1 integrins (Berditchevski and Odintsova, 1999;Berditchevski, 2001;Yunta and Lazo, 2003); the serine/threonine kinase PKCa (Berditchevski and Odintsova, 1999;Berditchevski, 2001;Zhang et al, 2001); B-cell receptors CD4, CD8, and CD19 (Imai et al, 1995;Mannion et al, 1996;Hammond et al, 1998); other tetraspanins including CD81, CD63, and CD9 (Vogt et al, 2002); receptor tyrosine kinases EGFR and ErbB2 (Odintsova et al, 2000(Odintsova et al, , 2003; an Ig super family molecule EW12 (Zhang et al, 2003b); and a newly identified tetraspanin molecule, kitenin, which is expressed in gastric cancers (Lee et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%